RANCANG BANGUN GAME ADVENTURE 3D UNTUK MELATIH HAFALAN SURAT PENDEK AL-QURAN - Timur, Dimas Maulana; Taurusta, Cindy; Astutik, Ika Ratna Indra (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Various alternatives and new innovations are needed to increase the effectiveness of providing applications that contain educational elements. One of them is the design of a 3D Adventure Game to practice memorizing short letters from the Koran which can help TPQ Al-Ikhlas students memorize and study short letters in a more fun and enjoyable atmosphere. The researcher chose TPQ Al-Ikhlas students as the target players, because TPQ Al-Ikhlas students had difficulty memorizing the Al-Quran due to the large number of verses, many verses that were similar but not the same, and also because they were not serious about memorizing the Al-Quran. The research method used is the Multimedia Development Life Cycle (MDLC) method which uses the research stages of concept, design, material collecting, assembly, testing and distribution. The research results of the 3D Adventure Game Design to Train Memorizing Short Letters of the Al-Quran went well with black box testing and user acceptance tests, this game has an average indicator of "Very Good" with a percentage of 84%. This shows that this game is suitable to be used as a learning medium for TPQ students to train their memory for memorizing short letters from the Koran.